The (non)linearity of religion and work motivation? Exploration across gender, age, marital, and employment status - Linando, Jaya Addin (Institut Agama Islam Negeri Langsa, 2024)
Religion and work motivation have been acknowledged as critical factors affecting workplace behaviors. While many studies have juxtaposed these two variables, the effort to really explore the connection between these factors is almost non-existent. Exploring the interconnection of these two factors is arguably essential either to understand workplace behavior to a greater extent or to enhance the sensemaking of religion–work motivation comprehension. The cross-sectional analysis involving 928 respondents from various religious affiliations suggests the linearity of religion–work motivation pairs. The present study concludes that intrinsic religiosity aligns with both identified regulation and intrinsic motivation; extrinsic religiosity–social aligns with extrinsic regulation–social; and extrinsic religiosity–personal aligns with introjected regulation.